Ipteks Pendampingan Desain Dan Renovasi Bangunan Taman Pendidikan Qur’an (TPQ) Al – Ashfa Dusun Rampal Desa Dadapan - Rini Pebri Utari; Erwin Rommel; Ernawan Setyono (I-Com: Indonesian Community Journal, 2024)
Al-Quran Education Park is a community group providing non-formal Islamic religious education which has an important goal of imparting religious knowledge to its students. TPQ AL Ashfa, which is located in Rampal hamlet, Dadapan village, Malang Regency, is one of the TPQs that was established in 2018. Until now, this TPQ has approximately 100 students with 4 teachers. The construction of the TPQ began with the provision of waqf land which was then built independently by the local community. In this service program, the service team collaborates with PMM Mitra Lecturer students to provide assistance with the design, physical work and arrangement of TPQ Al-Ashfa. The results are in the form of design of the talud/retaining wall, sanitation work, rebate work on the side yard of the TPQ so that it can be used as an outdoor facility, arrangement of the TPQ space, provision of assistance for supporting facilities for the TPQ program. With this assistance, TPQ becomes more neatly organized and the community and TPQ students can carry out the learning process comfortably and conducively.